Os sentidos da idade: morte e renascimento no processo de envelhecimento de mulheres executivas - Cepellos, Vanessa Martines (2016)
This research is inserted in a context of increasing female participation in the labor market, especially with regard to the rise of women to strategic positions, as well as an accelerated process of population aging, constituting one of the most significant changes in recent years. The participation of women in executive positions and the aging process are topics rarely approached in the academic literature, both isolated as interrelated, which justifies the originality of this work. These changes coincide even with the fact that it is the first time that women age in executive positions. Therefore, this research aims to explore how executive women experience the aging process. The discussion shows relevant to the extent that this woman is inserted in an organizational context of male dominance, predominantly young, where it is expected that the woman does not occupy strategic positions. The research is based on the theoretical perspective of social constructionism of Berger and Luckman (1999) and qualitative methodological approach (Grounded Theory), based on the symbolic interactionist perspective of Charmaz (2009). Data were obtained from 58 interviews with women aged 40 years or older who hold or have held executive position in organizations in Brazil. The research concludes that, for being considered older professionals rather than men and due the stigma associated with age, women tend to omit aging and look for ways to not appear in the workplace. Substantive theory shows that aging is understood from the notions of physical, social and business deaths and the symbolic rebirth is a way of dealing with the concepts of deaths that persist in the imagination of executive women. The theory is provisional and contingent and reflects the interpretation of a particular researcher. It is expected that will expand the management field of study and encourage researchers in the continuing investigation regarding the aging of executive women.